Preparation of jabuticaba cream as a strategy for the full use of the fruit: physical-chemical characterization and evaluation of bioactive compounds (Research, Society and Development, 2020)
The objective was to develop a formulation of jabuticaba cream  with the use of the whole fruit (pulp, peel, and seed) and to compare a formulation using only the seeded pulp. For both formulations the same ingredients were used, these were homogenized and subsequently frozen (-20 ° C ± 2). The physical-chemical characteristics, the content of phenolic compounds, anthocyanins, flavonoids, and carotenoids were evaluated in the final products. The jabuticaba creams were developed in three replications and the analyzes were carried out in triplicate. For the analysis of variance of the data obtained, statistics were performed using the R Core Team program (2017) and for the difference, the Tuckey test was applied with a 5 % probability. It was found that there was no statistical difference between the creams concerning the physical-chemical parameters, phenolic compounds (966.36 - 1620.89 mg EAG / 100g), and carotenoids (0.018 - 0.061 µg carotenoids/mg). However, the cream with peel showed higher values for the colorimetric parameters L *, C * and h * and for the average levels of flavonoids (16.26 mg / 100g) and anthocyanins (27.45 mg / 100g). The cream of jabuticaba added with peel is more beneficial because it can be an alternative for the full use of the fruit, thus avoiding the waste of the peels, which are rich in phytochemicals important not only for the coloring of the final product, which dispenses the use of synthetic dyes in the formulation, as well as for strengthening the immune system.